Fabrication of Eco-Friendly Pineapple Leaf Fiber-Based Vegan Leather for Environmental Sustainability - Siriwan Srisang; Jumpon Kunyuan; Thunyanat Hutangkoon; Orranat Eiangmee; Jatuphat Maikaew; Siwakon Sokjabok; Naruebodee Srisang (E3S Web of Conferences, 2026)
The environmental impact of synthetic leather production has raised global concerns due to its reliance on petroleum-based polymers and poor biodegradability. Therefore, the development of sustainable, eco-friendly alternatives using renewable resources has become increasingly important. A biodegradable vegan leather was developed from natural rubber and pineapple leaf fibers (PALF), with properties analyzed using Response Surface Methodology (RSM). The effects of fiber content (X1), compression time (X2), and compression temperature (X3) were studied on biodegradation (Y1), water absorption (Y2), and tensile strength (Y3). Results showed that all three factors significantly influenced Y1, with the predictive model demonstrating high reliability (R > 90%). The optimum condition for Y1 was X1 = 3.0 g, X2 = 70.0 min, and X3 = 110.0°C, yielding a maximum predicted biodegradation of about 21%. In contrast, the models for Y2 and Y3 were statistically unreliable (P > 0.05) due to low R² values. However, Y2 passed the lack-of-fit test, suggesting an adequate model form, while Y3 failed (P < 0.05), indicating an inadequate prediction model. These findings suggest future experiments should narrow factor ranges and include additional control variables to improve the predictability of Y2 and Y3. Despite these limitations, the study highlights a sustainable alternative to conventional synthetic leather, aligning with circular economy principles and supporting the United Nations Sustainable Development Goals (SDGs). Importantly, the process is resource-efficient: from 1 kg of pineapple leaves, only 20 g of fibers is obtained, and just 75 g of PALF was used in 15 experimental runs. This minimal material requirement underscores the potential of the approach for sustainable production, while highlighting potential applications in sustainable fashion, packaging, and eco-friendly product design.
Keywords: Collagen: Extraction and Characterization; Nanocomposite Films for Food Packaging; Advanced Cellulose Research Studies